Human body - Bingham, Caroline, 1962- (London ; New York : DK, 2003)
Full-color photographs and illustrations offer an introduction to the human body including the organs and cells that make up the body, the skeletal system, and the senses.
Includes index.
4.5
K-3
Keywords: Human body -- Juvenile literature; Human body; Sleep; Human body; Sleep